A Pragmatic Approach to Literary Interpretation of fiction with reference to the Merchant of Venice (Journal of the College of Basic Education, 2023)
The most important function of language is its communicative function as it used to convey ideas, feelings, attitudes, etc. yet, it also has other functions such as its expressive function as by which it is used to produce literary discourse. Literary discourse is a type of language use as such pragmatic theories of speech act and implicature can be utilized to analyze literary discourse of fiction. Literary fiction is a type of discourse that is characterized by its multi-layered discourse since there are two different, though interrelated, levels of interaction; where different sets of interlocutors interact with each other.The first layer involves interactions that take place among characters within the fictional discourse, whereas the other level involves the interaction in which both the playwright and the readers are engaged. These two levels are interrelated as the interaction between the playwright and the reader is guided by the interaction between among the characters inside the literary discourse.The theory of speech act could have some bearing on the literary interpretation of fiction as it can be applied to the double-level discourse in the fictional discourse. The theory of meaning and implicature can also be applied to this type of discourse to shed light on the way meaning can be retrieved and reached by the readers of fiction. The paper explores how pragmatic theories of speech act and meaning can of use in literary interpretation of fiction using excerpts from Shakespeare's The Merchant of Venice as data for analysis.